Contemporary issues in food supply chain management - Eastham, Jane (Oxford Goodfellow Publishers, 2017)
"This vital new text offers a holistic view of the factors affecting the different tiers of sustainability, public health, poverty, security and production within the food supply chain. With contributions from international experts in the field, it takes particular emphasis on growing populations and the deployment of agricultural land for uses other than food. Designed to examine issues facing the food supply chain, including food supply and security, Contemporary Issues in Food Supply Chain Management considers supply security in terms of food availability, traceability, the delivery of a sustainable diet, technological changes and the impact of current governance structures"--Provided by publisher.
Keywords: Food supply -- Management; Produce trade -- Management; Business logistics